Mehmed Talib-i Üsküdari’ nin divançe’ sinin edisyon kritiği - Engin, Ahsen (My University, 2002)
Mehmet Tâlib-i Üsküdârî'nin Divançesinin Edisyon Kritiği adlı çalışmamız, bir Celvetiyye tarikatı şeyhi olan Mehmed Tâlib Efendi'nin hayatını, eserlerini, tasavvufî mahiyetteki şiirlerini ve bu şiirlerin incelemelerini ihtiva etmektedir. Çalışmamızın Giriş bölümünde konuya hazırlık yapılarak tasavvuf ve edebiyata etkileri hakkında genel bir malumat verilmiş, Mehmed Talib Efendi'nin yaşadığı dönem olan XVII. yüzyıldaki Tasavvuf Edebiyatı kısaca gözden geçirilmiştir. Mehmed Tâlib Efendi'nin hayatıyla ilgili bilgiler Doğumu, Adı ve Mahlası, Tarikatı ve Şeyhleri, Vefat Tarihi, Eserleri başlıkları altında ortaya konmuştur. Divançenin incelenmesi, iki aşamada gerçekleşmiştir. Divançe önce şekil yönünden; şiirlerin şekilleri ve türleri, vezin ve kafiye özellikleri, dil ve üslûp özellikleri yönünden incelenmiştir. Eser içerik yönünden ele alındığında; şiirlerde işaret edilen ayet ve hadisler dipnotlarda numaralandırılarak gösterilmiş, yine şiirlerdeki tasavvufî unsurlar, tasavvufî mertebe ve makamlar, tasavvuf ile ilgili kavramların örnekleri dipnotlarda numaralandırılmıştır. Metinde tespit edilen deyimler alfabetik sıraya göre yazılmış, şiir numaraları belirtilmiştir. Divançedeki şiirler, transkripsiyon sistemiyle Lâtin alfabesine aktarılmıştır. Transkripsiyon sisteminin tablosu ayrıca çalışmaya ilave edilmiştir. Çalışmamız sırasında faydalandığımız eserler için bir bibliyografya hazırlanmıştır.

Our study, which is titled: The Edition Critique of Mehmet Talib-i Uskudari`s Divance* contains the biography of Mehmet Talib-i Uskudari who was a Celvetiyye Tariqa** sheikh and a close study of Uskudari`s different works and poems that are reflective of Islamic mysticism. At the initiation of the study, an introduction to Islamic mysticism and its reflections on Turkish literature along with a brief overview of the general characteristics of the Islamic mystic literature in 17th century, which is the period of time Mehmet Talib Efendi lived, is presented. The information on the life story of Mehmet Talib Efendi is compiled under the headings of His birth, name and his mahlas***; His Tariqa and His Tariqa sheikhs; His death and His works. The study of his Divance was carried out in two stages. Initially, the Divance was first scrutinized in terms of method; the types of poems and the methods that were adopted by the author in the creation of poems; meter, rhyme, language and style specifications that can be found within the respective bodies of these poems were detailed. While studying the Divance from the aspect of its contents, the verses in Quran and Hadiths**** that were pointed out in poems and Sufism related components of the poems such as hierarchical ranks and positions within the Sufi belief system were explained in numbered footnotes. Those idioms, which were determined to be within the texts, were written in alphabetical order and the numbers of the poems that those idioms are associated with were separately maintained. The poems within the Divance were translated into Latin alphabet with transcription system. The table of the transcription system is annexed to the study. Finally, a bibliography was prepared for the works that were utilized during the preparation of this study. * Divance: Poem books of poets. In these works, poets compile their poems in an order, the systematic of which is determined by them. It can be viewed as a sort of anthology. Şairlerin şiirlerini belli bir düzen içinde topladıkları kitaplardır. Bir tür antoloji olarak görülebilir ** Celvetiyye Tariqa: A Sufi path. Celvet literally means willingly departure of someone`s of his/ her place of residence, either hometown or country per se. In Islamic mysticism, it refers to someone`s stripping his soul from his body and make it disappear within in the existence of God. Celvetiyye Tariqa is a Sufi Path which is taken by people who are willing to commit the act of Celvet . Arapça'da yerini, yurdunu, terk etmek mânâsına gelen celvet kelimesi, tasavvuf dilinde, kulun halvetten çıkışı ve Allah'ın varlığında fanî oluşu anlamını taşır. Celvetiyye, Celvet eylemini gerceklestirme arzusunda olan insanlarin mensubu oldugu tarikata verilen isimdir. *** Mahlas: The nickname of the poet or the name he is famous for in the Ottoman literature. Osmanli edebiyatinda şairin takma adı, ya da tanındığı ad ****Hadiths: Sayings that are attributed to the prophet of Islam. Islam dininin peygamberine atfedilen sozler.
Keywords: Dil; Türk Dili; Türk Edebiyatı Eski-kaynaklar; Türkçenin gelişimi; Yeni türkçe (15.yy.-20.yy.)